The patterns of leprosy at Chris Hani Baragwaneth academic hospital - Nkehli, Lindinkululeko Jabulile (My University, 2020)
Background The World Health Organization announced a strategy to eliminate childhood leprosy infections, visible deformities and discriminatory legislation against leprosy patients by 2020. However, challenges in achieving a leprosy-free world and preventing neurological sequelae still exist. Human immunodeficiency virus (HIV) infection has been a challenging burden in our population. HIV-leprosy co-infection may result in an increased frequency of leprosy reactions without affecting the spectrum of leprosy. From 1921 to 1997 the leprosy prevalence remained less than one patient per 10 000 population. Current South African literature has very scanty information regarding the current situation of leprosy. Objectives The purpose of this research was to describe the trend of new leprosy patients from 1999 to 2015, including the demographics, clinical spectrum and treatment outcomes of patients treated for leprosy at Chris Hani Baragwanath Academic Hospital (CHBAH) during this period. Methods A retrospective review of patients’ clinical records was undertaken. Data on demographics, clinical spectrum including the leprosy classification, reactions, neurological involvement, HIV infection association as well as treatment outcomes were extracted. Data analysis was performed using descriptive and inferential statistics and a time series analysis. Results An upward trend from 1999 to 2001 was followed by a decline in the number of new patients. Eighty patients were registered over a period of 17 years, with a male-to-female ratio of 3:1. Thirty six patients were immigrants. Five were children less than 15 years old. Multibacillary leprosy was the most common type with 71 patients. Thirty six patients were lepromatous leprosy subtype, 22 were borderline-lepromatous, 13 were borderline-tuberculoid, six were midborderline and three were tuberculoid leprosy. Thirty one patients presented with reactions, type 1 in nine patients and type 2 in 21 patients with both types in one patient. Grade 2 neurological deformities were diagnosed in 37 patients, of which two were children. Eight patients were found to have HIV-leprosy co-infection. Out of 52 patients who completed treatment, 26 were cured and 26 were lost to follow-up. Twenty-one patients defaulted treatment while three patients relapsed. Conclusion This study highlights current status of leprosy in a low endemic centre with declining numbers of new patients. Multibacillary forms with grade 2 disabilities are common. The constant emergence of leprosy in our population highlights shortfalls in our control campaigns. Furthermore, a high rate of grade 2 disabilities necessitates scrutiny of education directed at early patient detection and follow-up strategies.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Medicine in Dermatology to the Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2020